Pedagogical Conditions of Effective Forming Communicative-Discursive Culture of the Future Officers-Border Guards during Their Study in Higher Military Educational Establishment of Border Department - Babich, Olha (Pedagogical Discourse, 2016)
In this article the main pedagogical conditions of formation of communicative and discursive culture of the future border guard officers in the study of humanities are defined as follows: 1) to use teaching methods that ensure mastering extralinguistic knowledge on the principles of crossrcultural communication. One important interactive method is a debate. Debate is a method of verbal discussion of material. It is a method of dialogue training and it has a specific search and activating peculiarities. Debate is carried out in the form of purposeful and well-prepared discussion between an instructor and the students. 2) development and usage of trainings for development of communicative and discursive culture components. Training provides the peculiarities of the interaction with representatives of other cultures and sets two main tasks. Firstly, through playing the situations that happen in different ways in different cultures to teach the cadets intercultural differences. Secondly, after cadets get acquainted with the most characteristic features of another culture, it’s necessary to transfer the acquired knowledge to other situations. 3) the usage of disciplinary connections to expand background knowledge and its usage by future border guard officers in professional activities. In general background knowledge is a collection of data and information about the specific features of the country, its national culture, the mentality of the people, national characteristics of verbal and nonverbal behavior. Therefore, background knowledge include the basic concepts that help to understand the socio-cultural context properly of a communicative situation, to interpret the content of the speech, behavior of verbal and non-verbal behavior of representatives of two cultures. Key words: pedagogical conditions, communicative and discoursive culture, method, training, background knowledgee, future border guard officer, discussion, debate.